Pistacia vera L. as natural source against antimicrobial and antiviral resistance - Mandalari, Giuseppina; Pennisi, Rosamaria; Gervasi, Teresa; Sciortino, Maria Teresa (Frontiers in Microbiology, 2024)
Increased global research is focused on the development of novel therapeutics to combat antimicrobial and antiviral resistance. Pistachio nuts represent a good source of protein, fiber, monounsaturated fatty acids, minerals, vitamins, and phytochemicals (carotenoids, phenolic acids, flavonoids and anthocyanins). The phytochemicals found in pistachios are structurally diverse compounds with antimicrobial and antiviral potential, demonstrated as individual compounds, extracts and complexed into nanoparticles. Synergistic effects have also been reported in combination with existing drugs. Here we report an overview of the antimicrobial and antiviral potential of pistachio nuts: studies show that Gram-positive bacterial strains, such as Staphylococcus aureus, are the most susceptible amongst bacteria, whereas antiviral effect has been reported against herpes simplex virus 1 (HSV-1). Amongst the known pistachio compounds, zeaxanthin has been shown to affect both HSV-1 attachment penetration of human cells, and viral DNA synthesis. These data suggest that pistachio extracts and derivatives could be used for the topical treatment of S. aureus skin infections and ocular herpes infections.